Igneous Rock Associations 17. Advances in the Textural Quantification of Crystalline Rocks - Higgins, Michael (Geoscience Canada, 2015)
During the last 20 years, textural (microstructural) studies have regained their place in the pantheon of petrographic methods. This has happened by quantifying textures, so that models can be developed and tested – an approach that has proved to be so successful for chemical and isotopic studies. The combination of chemical, isotopic and textural methods, especially if applied to different crystal populations, can be a very powerful tool in the clarification of petrologic histories of rocks. Here, I will discuss some recent advances in the application of textural studies to crystalline rocks.